Sufficient Conditions for Meromorphically p-Valent Starlikeness and Close-to-Convexity. (13th January 2013) - Frasin, B. A.; Al-Hawary, Tariq; Darus, M.
Abstract : Making use of the linear operator I λ m defined by (Frasin 2012), we introduce the class 𝕄 p, j m ( λ, μ, α ) of meromorphically p -valent functions in the punctured unit disk 𝒰 ∗ . Furthermore, we obtain some sufficient conditions for starlikeness and close-to-convexity for functions belonging to this class. Several corollaries and consequences of the main results are also considered.